The Antinomy of Kitsch: Kitsch as an Aesthetic Category and an Aesthetic / Art-Crititical Property - Lisa Katharin Schmalzried (ESPES)
The antinomy of kitsch comprises two conflicting yet widely accepted claims: first, kitsch and art are incompatible; secondly, some art is kitsch. The key to solving this contradiction is distinguishing between kitsch as an aesthetic category and an aesthetic, art-critical property. As an aesthetic category, kitsch is an artifact, performance, or practice whose dominant function is to enable self-enjoyment by effortlessly evoking emotional reactions of the “soft” emotional spectrum with a “sweet” phenomenological quality in a large group of people. Based on this definition, kitsch and art are two mutually exclusive aesthetic categories. As an aesthetic property, kitsch is the disposition to effortlessly evoke emotional reactions of the “soft” emotional spectrum with a “sweet” phenomenological quality by supervening on the kitsch typical features. So, everything kitsch is also kitschy, but not vice versa. Therefore, art can be kitschy, although it is not kitsch.